Multiphysics Simulation of Laser Cladding Process to Study the Effect of Process Parameters on Clad Geometry. (2016) - Parekh, Ravi; Buddu, Ramesh Kumar; Patel, R.I.
Abstract: The present work reports two-dimensional simulation of laser cladding process to understand the influence of process parameters on clad geometry formation for better process optimization. The application deals with pure copper powder cladding of SS316L substrate for process feasibility for thicker coating layers by CO2 laser. For this purpose, first mathematical model is developed and dealt numerically using multi-physics software. Conservation equation of energy, momentum and mass of this process are coupled through the temperature variable and solved to adapt the laser cladding process. The boundary conditions due to the laser melting process of dissimilar materials have to be deal with complex assumptions are applied in mathematical modelling to simplify problem due to the different materials properties. The deformation of free surface is calculated using moving mesh by the way of ALE (Arbitrary Lagrangian and Eulerian) method. In addition, thermo-capillary forces and their effect on fluid flow inside the melt pool are also considered in modelling to complete the process optimization. Thermal and stress distributions due to the process are also evaluated in the developed process simulation. The results provide approximate information about the effect of each selected parameters on clad geometry formation. The influence of process parameters have shown the best choice of optimization.